2018
DOI: 10.3390/ijms19041181
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient ABC_DE_Based Hybrid Algorithm for Protein–Ligand Docking

Abstract: Protein–ligand docking is a process of searching for the optimal binding conformation between the receptor and the ligand. Automated docking plays an important role in drug design, and an efficient search algorithm is needed to tackle the docking problem. To tackle the protein–ligand docking problem more efficiently, An ABC_DE_based hybrid algorithm (ADHDOCK), integrating artificial bee colony (ABC) algorithm and differential evolution (DE) algorithm, is proposed in the article. ADHDOCK applies an adaptive pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Koohi-Moghadam and Rahmani 24 used an enhanced DE algorithm with an LS algorithm and a pseudo-elitism operator to address the docking problem. Guan et al 25 introduced an efficient ABC_DE-based hybrid algorithm for protein-ligand docking, integrating artificial bee colony algorithm and DE algorithm.…”
Section: Related State-of-the-art Stochastic Optimization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koohi-Moghadam and Rahmani 24 used an enhanced DE algorithm with an LS algorithm and a pseudo-elitism operator to address the docking problem. Guan et al 25 introduced an efficient ABC_DE-based hybrid algorithm for protein-ligand docking, integrating artificial bee colony algorithm and DE algorithm.…”
Section: Related State-of-the-art Stochastic Optimization Methodsmentioning
confidence: 99%
“…Guan et al. 25 introduced an efficient ABC_DE-based hybrid algorithm for protein–ligand docking, integrating artificial bee colony algorithm and DE algorithm.…”
Section: Related State-of-the-art Stochastic Optimization Methodsmentioning
confidence: 99%
“…It was revealed that FIPSDock might be more suitable than the conventional GA-based algorithms in dealing with highly flexible docking problems. There are also some other docking algorithms using PSO variants as well as other optimization techniques, such as ant colony optimization (ACO), artificial bee colony (ABC), differential evolution (DE), and fireworks algorithm (FWA) as the search algorithms in AutoDock [22][23][24][25][26][27][28][29][30]. Although all the algorithms mentioned above have good performance in solving protein-ligand docking problems, it is still a challenge task due to the complexity of free energy landscapes and the accuracy and efficiency of docking [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…A number of variants based on AutoDock or AutoDock Vina were developed, in which the search algorithm is replaced by a metaheuristic algorithm. To name a few, SODOCK [ 8 ], PSO@AUTODOCK [ 9 ], FIPSDock [ 10 ], F l APCps [ 11 ], PSOVina [ 12 , 13 ], and ADHDock [ 14 ] have recently been published and have demonstrated superior performance over the basic AutoDock or AutoDock Vina methods. During the development of PSOVina, we realized that the main weakness of the original particle swarm optimization (PSO) algorithm is insufficient exploration of the search space.…”
Section: Introductionmentioning
confidence: 99%